A systematic literature review for the tourist trip design problem: Extensions, solution techniques and future research lines - José Ruiz-Meza; Jairo R. Montoya-Torres (Operations Research Perspectives, 2022)
The tourism sector represents an opportunity for economic growth in countries with tourism potential. However, new trends in global tourism require efficiency in tourism supply chain management. One of the main changes is the trend of personalized tourism, which includes the management of itineraries by the tourist. The tourist trip design problem is the problem associated with personalized trip design. This problem has been modeled in the field of Operations Research in different ways, being the Orienteering Problem the most widely applied in the specialized literature. The objective of this paper is to carry out a systematic review of the contributions made to the tourist trip design problem. A review taxonomy is proposed to analyze the main variants, objectives, and solution techniques. Also, future research lines are analyzed and proposed to enrich the literature and provide new solutions to real problems.
Keywords: 650; Tourism; Tourist trip design problem; Literature review; Taxonomy; Orienteering problem